2007
DOI: 10.1634/stemcells.2007-0657
|View full text |Cite
|
Sign up to set email alerts
|

Absence of OCT4 Expression in Somatic Tumor Cell Lines

Abstract: The POU-domain transcription factor OCT4 is associated with the pluripotent state of cells comprising the inner cell mass of pre-implantation embryos and has been known to play a critical role in the maintenance of pluripotency of embryonic stem cells. Reactivation of OCT4 expression is postulated to occur in differentiated cells that have undergone carcinogenesis, or tumor formation. In contrast to earlier studies, recent reports describe OCT4 expression in several human tumor cell lines. To resolve the appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 30 publications
(46 reference statements)
10
82
0
3
Order By: Relevance
“…Primer pairs designed to amplify only true POU5F1A and not its pseudogenes confirmed the expression of POU5F1A in embryonic carcinoma cells but failed to amplify PCR products from peripheral blood mononuclear cells (PBMNC), suggesting POU5F1A is not transcribed in these cells [20]. Indeed, we demonstrated that, like human PBMNC [21], human tumor cell lines [22], and murine mesenchymal stromal cells [23], neither the multipotent BM-MSC nor the non-UVSC in fact expressed detectable levels of POU5F1A protein.…”
Section: Discussionmentioning
confidence: 73%
“…Primer pairs designed to amplify only true POU5F1A and not its pseudogenes confirmed the expression of POU5F1A in embryonic carcinoma cells but failed to amplify PCR products from peripheral blood mononuclear cells (PBMNC), suggesting POU5F1A is not transcribed in these cells [20]. Indeed, we demonstrated that, like human PBMNC [21], human tumor cell lines [22], and murine mesenchymal stromal cells [23], neither the multipotent BM-MSC nor the non-UVSC in fact expressed detectable levels of POU5F1A protein.…”
Section: Discussionmentioning
confidence: 73%
“…The absence of staining in pulmonary carcinomas for OCT-4, an embryonic stem cell marker, is confirmatory. 35,36 The OCT-4 staining is positive in germ-cell tumors, such as seminomas and embryonal carcinomas, but not in somatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not observe expression of any of the other pluripotencyassociated genes in MCF7-derived spheres, consistently with the results obtained in human tumours. Despite some reports claiming expression of Oct4 and Nanog in breast carcinoma cell lines, expression of several pseudogenes have been reported for both Oct4 and Nanog (Suo et al, 2005;Zhang et al, 2006;Cantz et al, 2007;Ambady et al, 2010), therefore, particular care must be taken to avoid PCR amplification of those pseudogenes. We base our conclusions in antibodybased assays, thus, looking specifically at the protein level to avoid pseudogene detection.…”
Section: Sox2 Activation In Breast Cancer Stem Cellsmentioning
confidence: 96%